Identifikasi Flavonoid Pada Ekstrak Bunga Kembang Merak (Caesalpinia Pulcherrima) Dan Aplikasinya Sebagai Indikator Asam Basa - Irwan, Irwan; Supriadi, Supriadi; Sakung, Jamaluddin (Universitas Tadulako, 2014)
Kembang merak flower (caesalpinia pulcherrima) is one of the ornamental plants, easily cultivated and its colour is yellowish red which also containing flavonoids. This research aims to identify the flavonoid compounds of kembang merak flower as acid-base indicator. It was done through the extraction of Kembang Merak using methanol as solvent. The extract separated by thin layer chromatography (TLC) using the eluent of BAA (butanol : acetic acid : water) (4 : 1 : 5) as an appearance of stains used ammonia vapour. TLC kromatogram results showed that there were two components with Rf 0.58 and 0.89. Both of the components separately scarapped then dissolved in methanol and measured absorbance at a wavelength 0f 200-600 nm using UV-Vis spectrophometer T80. Component I identified as isoflavones, khalkon, and auron whereas component II identified was not. For the comparison of kembang merak in solution of acid was red and base was green. The titration of strong acid-strong base of the kembang merak extract have have changed the colour in pH 9.51-11.38 pink to green, while titration of a weak acid-strong base have change the colour of light orange to green at pH 9.22-11.59 and for titration of strong acid-weak base colour changing light greenish into orange with a pH range from 2.73 to 1.93. The extract of kembang merak flower can be applied phenolphthalein has been applied.